The value of domestic subsidy rules in trade agreements - Michael Ruta; Daniel Brou; Edoardo Campanella (World Trade Organization (WTO), 2009)
This paper investigates the efficient design of rules on domestic subsidies in a trade agreement. A clear trade-off emerges from the economic literature. Weak rules may lead Member governments to inefficiently use domestic subsidies for redistributive purposes or to lower market access granted to trading partners once tariffs are bound. On the other hand, excessive rigidity may inhibit tariff negotiations or induce governments to set inefficiently high tariffs, as strict regulations would reduce policy makers' ability to use subsidies to offset domestic market distortions. Efficient subsidy rules are, therefore, the ones that strike the right balance between policy flexibility and rigidity. This economic approach provides a framework to interpret the provisions on domestic subsidies in the WTO.
Keywords: F13; F55; H25; D72; 330; WTO/GATT; Subsidy Rules; Trade Agreements; Trade Policy Credibility; Handelsabkommen; Subvention; WTO-Regeln; Internationale Handelspolitik; Glaubwürdigkeit